Analisis Pesan Edukasi Akun TikTok Dokter Detektif Tentang Kasus Overclaim - Desy Rahmawaty; Pinkan Zehrazeti; Dewi Jayanti; Ali Imron (Journal of Communication, 2025)
This research aims to analyze the educational message conveyed by Detective Doctors regarding overclaim cases in skincare products. The overclaim phenomenon often occurs in the marketing of beauty products, where the claims conveyed exceed the actual benefits. Education from medical personnel, as done by Doctor Detective, is one of the efforts to increase public awareness of this issue. This research uses the content analysis method to examine educational messages delivered through digital platforms. Research results show that the message conveyed has three main elements: the disclosure of scientific facts, the dismantling of exaggerated claims, and the delivery of health-based education. This finding shows that a clear, fact-based, and educational communication approach is effective in increasing people's literacy about the safety of skincare products. This research is expected to be a reference for health practitioners and beauty industry actors to convey information honestly and responsibly.